2019
DOI: 10.1038/s41598-019-45735-6
|View full text |Cite
|
Sign up to set email alerts
|

Methodical inaccuracy of the Z-scan method for few-cycle terahertz pulses

Abstract: Modern sources of THz radiation generate high-intensity pulses allowing to observe nonlinear effects in this spectral range. To describe many nonlinear effects theoretically, it is necessary to know the nonlinear refractive index coefficient of optical materials. The work studies the applicability of the Z-scan method to determine the nonlinear refractive index coefficient in the THz frequency range for few-cycle pulses. We have discussed the correctness of the known Z-scan method for calculating the nonlinear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The magnitude of the difference between the maximal and minimal values allows to calculate the nonlinear refractive index coefficient. Earlier we have shown that this technique is applicable for THz frequency range featuring a very broad spectrum with the correct ratio of the crystal thickness to the spatial size of the pulse [40]. Regarding water as the nonlinear medium, we obtained theoretically a value of n 2 = 5×10 −10 cm 2 /W and experimentally n 2 = 7 ± 5 × 10 −10 cm 2 /W.…”
Section: Discussionmentioning
confidence: 73%
“…The magnitude of the difference between the maximal and minimal values allows to calculate the nonlinear refractive index coefficient. Earlier we have shown that this technique is applicable for THz frequency range featuring a very broad spectrum with the correct ratio of the crystal thickness to the spatial size of the pulse [40]. Regarding water as the nonlinear medium, we obtained theoretically a value of n 2 = 5×10 −10 cm 2 /W and experimentally n 2 = 7 ± 5 × 10 −10 cm 2 /W.…”
Section: Discussionmentioning
confidence: 73%
“…Routine z scan measurements are obtained either with an open or a partially closed aperture in front of the detector [23]. Often, z scan experiments measure only the transmitted intensity with, e.g., a bolometer or a diode, and not the field transmittance [26][27][28]. An open aperture intensity z scan allows to quantify only the nonlinear absorption (α NL ) [26], while a partially closed aperture intensity z scan is sensitive both to the nonlinear absorption as well as the nonlinear refraction [26].…”
Section: Resultsmentioning
confidence: 99%
“…Tcypkin et al [23] reported the nonlinear transmission of almost single-cycle pulses centered at 0.75 THz by a liquid water jet. They performed typical z scan measurements [26], whereby the sample is moved through the beam focus and the intensity transmission is measured with a power detector, both with an open as well as with a partially closed aperture [27,28]. This experimental approach is restricted to the large sample volume required to run a recirculating liquid jet, which to our knowledge needs at least hundreds of milliliters of liquid sample [29].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid progress of intense THz sources and detectors has motivated researchers to use intense THz radiation for various applications. Since intense THz pulses can provide higher energy for photoexcited carriers, many studies use intense THz radiation for THz time-domain spectroscopy (TDS) to characterize the carrier dynamic properties of semiconductors and other condensed matter systems [106][107][108][109][110][111][112][113][114][115][116][117][118][119]. Additionally, intense THz radiation has a relatively high peak electric-field strength that allows various traditional optical nonlinear effects such as high-order harmonic generation [110,111], saturation and anti-saturation absorption [112][113][114][115][116], and four-wave mixing.…”
Section: Applications Of Intense Terahertz Radiationmentioning
confidence: 99%